The ecology of learning : sustainability, lifelong learning and everyday life - Blewitt, John, 1957- (Earthscan, 2006)
Your house is flooded by 'unseasonal' heavy rain. What do you learn from this experience? Do you shrug your shoulders and call your insurer? Or do you choose to learn about climate change, switch to renewable energy and lobby politicians? In this insightful book, John Blewitt explores the possibilities for developing a sustainable society through 'lifelong learning'? that is, learning that happens in everyday environments and activities as diverse as shopping, community, 'edutainment', information and communication technology, the internet, broadcasting, people's experience of place and space.